TRANSISI KEHIDUPAN EKONOMI MASYARAKAT WISATA KAMPUNG TOPENG, TLOGOWARU, MALANG - Waqi’atul Aqidah (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2020)
Desaku Menanti program from Indonesian Ministry of Social Affairs has been implemented by Malang City Social Service in the form of the development tourism village the named is Wisata Kampung Topeng in Tlogowaru, Kedungkandang, Malang City. This tourism village is realized as an effort to empower homeless people, such as beggars, buskers, and scavengers. These fostered residents are given variety of facilities and social assistance to meet their primary needs. Society is given guidance and assistance in the form of training and funding business.This research uses qualitative method which type is phenomenological research. Determination of research location uses a purposive area method, in Baran Hamlet, Tlogowaru Village, Kedungkandang, Malang City. The research subjects were determined by purposive sampling, Malang City Social Service and Kampung Topeng Tourism Community. Data collection in this study uses interview, observation, and document. Analysis data used by researcher consist of three tools, data reduction, data presentation, and conclusion.This community economic empowerment program as intended to improve community welfare and support economic activities of society. In the process of empowerment, the community face economic transition. Various jobs and efforts the have do to improve a better quality of life. The community is able to be more productive in encouraging and more rational in consumption activities. In addition, the ability of the community to prioritize needs appears in better financial management. Keywords: economic empowerment , financial management.